Narrative Formation and its Role in Introducing the Protagonist The Novel (Minor Murder Epic) a Model - Al_ Shekh Hossein, Hameeda (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Arab criticism has accessed a phase in which the tendency to changing the diction of dealing with the text whether it was narrative or verse was an urgent necessity. The most important aspects of this change are shown in the interest in what is called (Form), the non-separation between the content and the context, revealing the internal secrets of texts in an attempt to refreshing the point of view to the narrative text and dealing in a different way with its structure throughout making a reading variety derived from the common and the uncommon modern critical theories. The interest in studying narrative structure on top of the critical researches involved in novel which take part in introducing critical processing that analyses texts and aims to uncover them away from mental – social and historical references that go-round them.